Development Probiotic Food Based on Rice Brand - Zubaidah, Elok (Jurnal Teknologi Pertanian, 2006)
Rice bran is one of the sources of bioactive components and is therefore a good raw material for functional food. It contains inositol, ferulat acid, fitosterol, orizanol, tocotrienol, cholin, and fibre and considered as nutraceutical food. A rice bran-based functional food may be developed by fermenting it in combination with milk using probiotic, such as L. casei. A randomized block design research was performed to determine the best ratio of skim milk to rice bran in the making of rice bran-based fermented drink. The ratios of the skim milk to rice bran evaluated were 12:0, 8:4, 4:8, and 0:12 respectively. The experiment was made in   a triplicate. The results showed that the ratio of skim milk to rice bran significantly affect on the viability and antimicrobial activity of L.casei during fermentation process. The highest viability and antimicrobial activity was found on the fermentation medium which contained rice bran only. The fermented product contained L. casei  at  a level of 2,9x109 cfu/ml,  a total acidity of  1,003% and   pH 4,267. It was found that the antimicrobial activity was 0.245, measured as a turbidity value. Key word: Rice bran, Fermented milk, Lactobacillus casei